Characterization of the "banco", a building material for tropical and rural environment - GIBIGAYE, Mohamed (My University, 2015)
The population's access to comfortable modern accommodation and food security are major issues in developing countries [1]. To achieve these objectives, the use of local building materials associated with agricultural by-products is a solution for the future. This work focuses on the valorisation of local building materials in Benin to provide to the people of modern, comfortable accommodation and lower cost. The studied material is composed of a mixture of stems of rice, clay soil, and the infusion of nere which are all traditionally used for construction in rural areas, especially Northern Benin [2, 3]. Our study therefore focused on characterization physical, mechanical and thermal composite material called, “banco granary.” The land of bar that can be used in the banco is available in the municipality of Abomey-Calavi. The resistances tension by bending and simple compression of the banco are 2,188 MPa and 4,948 MPa, respectively. Furthermore, the punching-bending strength (NF EN 15037) at 28 days, of blocks in banco in length 50 cm is 210,762 daN, significantly greater value than specified by the standard. Which allows the use of blocks in banco and resistant semi renderd in floors in blocks and beams. Also we obtained from the thermal tests, the values of conductivity, the effusivity and thermal diffusivity for two formulation methods. In general, these thermal properties increase proportionally to humidity. The conductivity values obtained are all below that of a brick. That confirms the improvement of the conductivity of the banco by the contribution of the stems of rice.
Keywords: Banco; composite material; characterization; building material; rural environment